Investigating the Impact of COVID-19 on the Performance of Indian Mutual Fund Schemes: An Investors Perspective - Ajmera, Mr. Gaurav; Jha, Dr. Babita; Sharma, Dr Sudhi (The journal of contemporary issues in business and government, 2021)
The outbreak of Coronavirus has battered the Indian economy and IMF has projected that the growth rate of India will contract by 4.5 percent in this fiscal year. The market sentiments over the last few months have gone down. Financial markets are adversely affected by this pandemic and the mutual fund industry is no more exception. The mutual fund industry is facing high volatility due to this turmoil. This paper, therefore, aims to study empirically the impact of COVID -19 on diverse aspects of different schemes of mutual funds. The paper is divided into two parts i.e. the first part has analyzed mutual fund schemes from the perspective of several folios, redemption/repurchase, and cash flows. The second part of the paper empirically drives the impact of COVID-19 on various schemes of mutual funds by applying econometric dummy variable regressions. The study concluded that COVID-19 has largely impacted the large-cap schemes rather than mid and small-cap schemes. Further, funds i.e. DSP Midcap fund, Axis Small-Cap, and Kotak Small-Cap funds had shown the positive impact of the crisis on the Net Asset Values (NAVs) of the funds. Therefore, the investors long in other schemes could take a short position in these schemes to get a considerable hedge against probable losses.